Amulet : Waverider - Book 9 Book nine, Waverider - Kibuishi, Kazu, 1978- (New York, NY : Graphix, an imprint of Scholastic, 2024)
"After her confrontation with Ikol, Emily finally understands the stone's power and what she must do to defend Alledia from the shadows. As she travels to Typhon to help her mom and Navin, Prince Trellis returns to the Kingdom of the Elves to save his countrymen--and confront the fraud who has seized power in the absence of a king. The threat of darkness follows all Stonekeepers closely, and it will take the strength of both new friends and old foes to conquer it--and survive"--
Keywords: Siblings -- Comic books, strips, etc; Amulets -- Comic books, strips, etc; Charms -- Comic books, strips, etc; Elves -- Comic books, strips, etc; Imaginary places -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Siblings -- Fiction; Amulets -- Fiction; Charms -- Fiction; Elves -- Fiction; Imaginary places -- Fiction; Magic -- Fiction; Cartoons and comics; Graphic novels; Fantasy comics